The Retention of Experienced Faculty in Online Distance Education Programs: Understanding Factors that Impact their Involvement - Green, Tim; Alejandro, Jeffery; Brown, Abbie H. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
The study sought to determine factors that affect faculty decisions regarding their involvement in teaching online distance education courses. A survey was administered to online distance education faculty across the United States to determine those factors that encourage or discourage them from continuing to teach online courses. The factors were examined and reported from the standpoint of each of four faculty groups: (1) tenured, (2) tenure-track, (3) full-time non-tenured/fixed term, and (4) part-time/adjunct. From the survey responses (N = 135), a list of retention strategies that university administrators may use for retention of online distance education faculty are offered.